SPRICHWÖRTER, GEFLÜGELTE WORTE UND ZITATE ALS MOTTI IN DEM BUCH BREXIT: EINE BILANZ VON RUDOLF G. ADAM (2019) - Gläser, Rosemarie (Proverbium - Yearbook, 2020)
The article is intended to analyse the sources and functions of mottoes to chapters in political publications as presented in the topical book BREXIT. Eine Bilanz by Rudolf G. Adam (2019). This German author worked as an adviser, diplomat, (vice)president, academic teacher and writer in many fields and was associated with influential national and international institutions. His close connection with life and culture in the United Kingdom for more than 60 years, and with Britain’s relationship towards the European Union which resulted in the Referendum on June 23, 2016, provide the background for Adam’s critical book BREXIT. The mottoes to each sub-chapter as intertextual links have been drawn chiefly from British and American literature. They constitute an essential structural element throughout this book and bear witness to the author’s pro-found knowledge and personal historical commitment. In addition to mot-toes, he uses proverbs, quotations, maxims, slogans and proverbial sayings also in the following text. In this respect, the exposed mottoes and the traditional phraseological expressions in their textual environment are striking stylistic features of R.G. Adam’s linguistic portrait.